Kejadian Kasus Kebakaran di Rumah Sakit di Indonesia Tahun 2020 Sumber Melalui Media Online - Ahmad Farid Umar (Jurnal Persada Husada Indonesia, 2020)
Hospitals are one of the places that have a fire risk. It is estimated that in the United States each year from 2012 to 2014 there were 5.700 fire cases in health facilities and 1100 of them occurred in hospitals. This study aims to examine the incidence of fires in several hospitals in Indonesia, the data obtained from online media. This type of research is a case study using qualitative methods. The data used in the search for fire cases in hospitals is data published in Indonesian online media, which was published from January 1, 2020 to December 31, 2020. The variables studied were the time, the city where it occurred and the part affected by the fire incident at the hospital. The results showed that hospital fires occurred in 7 (seven) cities/districts in Indonesia. The cities where the fires occurred twice were in Jakarta, twice in Surabaya and one time each in Semarang, Yogya and Bekasi Regency. The fire incident at the hospital occurred between July and October, which is the dry season in Indonesia. Most of the time the fire occurred was above 14.00 pm (three times), around 17.00 pm was twice, once at 11.00 am and once at 5.00 am in the morning. The burnt section on the ground floor, air conditioning in the laboratory room, pharmacy building, radiology, warehouse, adult treatment room, and electrical panels and generators. All of these locations are prone to fire.